Corpus Linguistics for education a guide for research - Pérez-Paredes, Pascual (Routledge corpus linguistics guide, 2021)
Corpus Linguistics for Education provides a practical and comprehensive introduction to the use of corpus research-methods in the field of education. Taking a hands-on approach to showcase the applications of corpora in the exploration of educationally relevant topics, this book:* covers 18 key skills including corpus building, the role of frequency, different corpus methods, transcription and annotation;* demonstrates the use of available corpora and desktop and online corpus analysis tools to conduct original analyses;* features case studies and step-by-step guides within each chapter;* emphasises the use of interview data in research projects.Corpus Linguistics for Education is an essential guide for students and researchers studying or conducting their own corpus-based research in education